KIT genetic alterations in anorectal melanomas. Issue 2 (14th November 2014) - Santi, Raffaella; Simi, Lisa; Fucci, Rossella; Paglierani, Milena; Pepi, Monica; Pinzani, Pamela; Merelli, Barbara; Santucci, Marco; Botti, Gerardo; Urso, Carmelo; Massi, Daniela
Abstract : Background: Mucosal melanomas (MM) represent a heterogeneous tumour population that exhibits site-specific molecular profiles. Aims: In a multicentre retrospective study, we investigated KIT aberrations in primary anorectal (AR) melanomas compared with melanoma metastatic to the gastrointestinal (GI) tract. Methods: Primary AR MM (n=31) and GI metastatic melanoma (n=27) were studied for KIT mutations on exons 11, 13, 17 and 18 by high-resolution melting analysis, direct sequencing and c-KIT expression by immunohistochemistry. Selected cases were also investigated for increased KIT gene copy number by fluorescent in situ hybridisation. Results: Functional KIT mutations were demonstrated in 11/31 (35.5%) of AR melanomas and in 1/26 (3.8%) of GI melanoma metastases (p=0.004). A significant difference emerged between primary and metastatic MM with regards to KIT-positive immunostaining (p=0.002). Immunohistochemical c- KIT protein overexpression did not correlate with KIT mutational status. Increased KIT copy number was demonstrated in 5/20 AR primary cases. Conclusions: The rate of functional mutations in KIT is significantly higher in AR MM than in GI metastatic melanoma. KIT protein overexpression does not correlate with KIT mutations and cannot be used for screening purposes. Recognising the molecular heterogeneity of MM helps to identify patients who require a different therapeutic approach.